Imperial Gamble : Putin, Ukraine, and the New Cold War - Kalb, Marvin L. (Book collections on Project MUSE., 2015)
"In Imperial Gamble: Putin, Ukraine, and the New Cold War, Marvin Kalb brings to life the geography, power politics, and history of Ukraine -- once known as Kieven Rus', or the 'First Russia.' He takes a critical look at the tortured history of post-Soviet Russia and Ukraine, and the journeys deep into the Russian past to uncover the roots of Russian and Ukrainian nationalism. Kalb maintains that world order hangs on a resolution of the Ukraine crisis, and he makes the provocative argument that the only sensible solution lies in both Russia and Ukraine recognizing that their futures are irrevocably intertwined. Any realistic solution must take into account the national interests of both nations. The West can approve or disapprove, but the two countries must reach their own modus vivendi. This is a time for realpolitik; and if the West continues to intrude into this delicate game of diplomatic shadow-boxing the effort will very likely collapse."--Provided by publisher.